Auto del Tribunal Superior de Medellín: Citibank vs. Garces Soto E. - Velásquez Osorio, Nydia; Zapata Rubio, Abel; Carvajal Arbeláez, Bernardo; Uribe Suárez, Harlen (Estudios de Derecho, 1980)
Auto del Tribunal Superior de Medellín: Citibank vs. Garces Soto E.